(untitled) (Revista Rupturas, 2022)
This articule aims to present a first approach focused on understanding of youth as a relational structure that is built from three pillar principles, namely: reproduction, dialogue or negotiation and confrontation or conflict against the adult. Through a scientific essay, carried out from a qualitative approach and an interpretative scope. In this way, various configurations of concepts such as youth are discussed. Far from being limited to describing a process of opposition to everything that refers to the adult world or responding to their stereotypes, this concept and the demographic sector which belongs to it, express in their dynamics the composition of the society and historical moment in which it is analyzed.